Karyotype analysis of seven species of the tribe lophiohylini (Hylinae, Hylidae, Anura), with conventional and molecular cytogenetic techniques - Gruber, Simone Lilian [UNESP]; Haddad, Célio Fernando Baptista [UNESP]; Kasahara, Sanae [UNESP] (Pensoft Publishers, 2012)
Few species of the tribe Lophiohylini have been karyotyped so far, and earlier analyses were performed mainly with standard staining. Based on the analysis of seven species with use of routine banding and molecular cytogenetic techniques, the karyotypes were compared and the cytogenetic data were evaluated in the light of the current phylogenies. A karyotype with 2n = 24 and NOR in the chromosome 10 detected by Ag-impregnation and FISH with an rDNA probe was shared by Aparasphenodon bokermanni Miranda-Ribeiro, 1920, Itapotihyla langsdorffii (Duméril and Bibron, 1841), Trachycephalus sp., T. mesophaeus (Hensel, 1867), and T. typhonius (Linnaeus, 1758). Phyllodytes edelmoi Peixoto, Caramaschi et Freire, 2003 and P. luteolus (Wied-Neuwied, 1824) had reduced the diploid number from 2n = 24 to 2n = 22 with one of the small-sized pairs clearly missing, and NOR in the large chromosome 2, but the karyotypes were distinct regarding the morphology of chromosome pairs 4 and 6. Based on the cytogenetic and phylogenetic data, it was presumed that the chromosome evolution occurred from an ancestral type with 2n = 24, in which a small chromosome had been translocated to one or more unidentified chromosomes. Whichever hypothesis is more probable, other rearrangements should have occurred later, to explain the karyotype differences between the two species of Phyllodytes Wagler, 1830. The majority of the species presented a small amount of centromeric C-banded heterochromatin and these regions were GC-rich. The FISH technique using a telomeric probe identified the chromosome ends and possibly (TTAGGG)n-like sequences in the repetitive DNA out of the telomeres in I. langsdorffii and P. edelmoi. The data herein obtained represent an important contribution for characterizing the karyotype variability within the tribe Lophiohylini scarcely analysed so far. © Simone Lilian Gruber et al.
Keywords: Ag-NOR; Amphibian cytogenetics; C-banding; Fluorochrome staining; rDNA probe; Telomeric probe